Content Analysis of Policymaking Process in Accounting and Presenting a Novel Approach in Light of Chaos Theory - Masoumeh Kazemi Nojedeh; Ali Akbar Nonahal Nahr; Heydar Mohammadzadeh Salteh (بررسی‌های حسابداری و حسابرسی)
Objective The foundation of accounting knowledge has always been to provide essential information for users to make informed economic decisions. However, evidence suggests that the standards derived from the current policy-making process prevalent in accounting fail to be notably effective in providing valuable information for decision-making, especially for investors. The primary cause of this inefficiency and ineffectiveness in accounting policy-making stems from the dependence on linear reasoning. The policy-making process in accounting is plagued by an array of contradictions, disorders, repetitions, challenges, and provisional agreements among groups without a logical and unified framework. This research aims to analyze the content of the policy-making process in accounting and present a novel approach to rectify this process and strategically guide it towards fulfilling its objectives in light of the chaos theory. Methods This study adopts a mixed-methods research approach. Initially, content analysis was employed to extract components affecting patterns in the policy-making process. Specialized questionnaires tailored to these identified components were subsequently distributed to gather the opinions of experts. These questionnaires were crafted to evaluate both the prevailing policy-making process in accounting and the decision-making behaviors of accounting information users, especially those of investors. The statistical population consists of certified accounting experts, i.e., practicing auditors affiliated with the Iranian Association of Certified Public Accountants, Accounting Faculty members, accountants affiliated with the Iranian Institute of Certified Accountants, and other experts in the accounting policy-making process, its standards, and the economic decision-making process. Purposive sampling was then employed to select the participants. Out of 60 distributed questionnaires, 42 were completed and returned. Single-sample t-tests and regression analysis were then conducted to analyze data. Results The research findings indicate that the investors’ decision-making process inherently follows a nonlinear pattern, whereas the accounting policymaking process has traditionally followed a linear approach. Therefore, as long as this inconsistency exists, there can be no improvements or changes in recognizing the informational needs of various user groups, establishing clear standard-setting directions, aligning standards with user needs, and avoiding crafting contradictory accounting standards, leading to a regressive and ineffective cycle. Furthermore, the use of the chaos theory principles can guide the accounting policymaking process toward a both realistic and efficacious trajectory. Conclusion The financial events and informational demands of accounting information users follow complex, ever-evolving nonlinear dynamics. Therefore, integrating the chaos theory methodologies into the accounting policymaking process can facilitate the development of effective standards that cater to the decision-making needs of accounting information users and fulfill the ultimate objectives of accounting knowledge.